Interplay of Data in Digital Economy and Merger Control Regime: A Conundrum without Solutions - Singh, Kritika; Mishra, Sarthak (Law, State and Telecommunications Review, 2022)
[Purpose] The paper is an attempt by the authors to evaluate the feasibility of applicability of existing competition law framework to the growing platform economies and the resultant implications of personal data being collected by such entities. [Methodology/approach/design] The present research is doctrinal in nature and the authors have adopted a comparative-analytical research methodology for evaluating the research questions. For the purpose of brevity, the authors have identified three research questions which shall form the basis of the research. Firstly, what is the inter-relation between the growing platform economy and merger control regime of a country. Secondly, what the possible avenues of concerns that may arise due to collection of personal data. Lastly, what are the possible enforcement challenges that would hampering the applicability of existing competition regimes to the digital platforms. The authors have considered the jurisdictions of EU and India as the geographical scope for the research, whereas, the subject-matter scope of the present research is limited only to the facets of interaction between the merger control regime and the abusive conduct of a dominant enterprise in the arena of digital markets. [Findings] The authors have made the following observations upon the conclusion of the study. First of all, the use and access of this data after the merger with companies with low turnover confer the acquiring enterprise a market power by which it can have an edge over its competitors in the market which will ultimately harm the competition in the market. Second, the digital market is data-driven, hence, collection of copious amounts of data, places the big-tech players in a position of control, allowing them indulge in exclusionary and exploitative conduct. Third, the assessment basis of combinations, more specifically in cases of data-driven mergers within the competition law needs a serious re-assessment, so as to include monetary value of data within the scope of assessment, as it is primary asset in such cases. [Practical implications] The importance of this research lies in the acknowledgement accorded the issue and the existing loopholes with the current merger control framework concerning data-driven mergers. Hence, the assessment criteria provided within the paper for the data-driven mergers would effectively serve as a foundational study for the further evolution and development of a specific and concrete framework for regulating data-driven mergers.